ЗАПОБІГАННЯ БАНКРУТСТВУ ПІДПРИЄМСТВ ЯК СКЛАДОВА СТАЛОГО РОЗВИТКУ - Nusinov, V.Ya.; Oliukha, V.G.; Burkova, L.A.; Shepeliuk, V.А. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2021)
Sustainable development of the enterprise is characterized by stable, balanced functioning of its three subsystems – economic, social and environmental. However, development is impossible without ups and downs, which disrupts stability. Recently, the spread of the pandemic has had a negative impact on the world economy and jeopardized the level of its sustainable development. In Ukraine, the impact of the pandemic has exacerbated the crisis due to the stratification of the unstable economic and political situation in the country. As a result, this led to a rapid growth in the number of unprofitable enterprises. Statistics show an increase in the number of initiated bankruptcy proceedings of enterprises and even their liquidation due to insolvency. The article hypothesizes that development cannot occur constantly, and therefore does not exclude the possibility of volatile states. Unsustainable development of the enterprise is characterized by its financial insolvency, which is identified with its bankruptcy. At the same time, bankruptcy of enterprises in Ukraine is quite common. Bankruptcy of the enterprise – the inability of the debtor to restore its solvency through the procedure of rehabilitation and restructuring and is a consequence of unsustainable development. It arises due to external (economic, scientific and technical, political, legal, international, environmental, pandemic, infrastructural) and internal factors (poor management of the founders of the debtor and its management). Internal factors are the main ones. Economic and legal means that can help identify in the early stages of negative trends in financial condition and prevent them – the development plan of the enterprise. One of the components of this plan is the economic analysis of the financial condition of the enterprise. The legislator has significantly simplified the requirements for filing a lawsuit to declare a company bankrupt. This can lead to abuse of the right to file such a lawsuit (raider seizures, tax evasion and unfair competition). In our opinion, a safeguard against abuse can be not only certain restrictions for the initiating creditor in the right to file for bankruptcy, but also the establishment by the legislator of increased liability for him in case of establishing the facts of abuse of such a right. In addition, the article emphasizes that the current methodological approaches to assessing the probability of bankruptcy of enterprises do not allow establishing the approach of this event taking into account the time factor, but only indicate the possibility of its occurrence. In this case, the range of possible time affects the choice of top management of urgent measures to correct the financial condition of the enterprise, the implementation of which will prevent the opening of bankruptcy proceedings or to delay the likelihood of its occurrence. The proposed methodological approaches allow determining the probability of bankruptcy of Ukrainian enterprises in order to predict the development of events in the early stages of bankruptcy. REFERENCES